Physiologic Change in Hypoglycemia in Diabetes Patients in Rajavithi Hospital Using Non-Invasive Hypoglycemic Warning Wearable Devices: A Pilot Study - Niramitmahapanya, Sathit; Yotha, Dararat (International Journal of Innovative Research in Medical Science, 2021)
Background: Hypoglycemic events are serious side effects which can occur when intensive glycemic control is being used to prevent vascular complications in diabetic patients. A wearable device which warns of impending hypoglycemia may help to achieve better control of diabetes. Objective: To identify physiologic changes during hypoglycemic events in diabetic patients using a wearable device. Materials and Methods: This was a pilot study of 28 glycemic events from 10 participants who used wearable hypoglycemic devices with Continuous Glucose Monitors (CGMs) in order to confirm hypoglycemic events during the study period. Variations in skin body temperature, pulse rate and skin resistance were also analysed. Data from the wearable hypoglycemic devices were collected and compared with those from CGMs to find significant variables during the hypoglycemic events. Results: Decrement of body temperature (Min BT-Mode BT) was greater in the hypoglycemic event group (-1.73±2.07 compared to -0.07±0.51in the non-hypoglycemic event group). Increment of heart rate (Max HR-Mode HR) was also higher in the hypoglycemic event group at 30.57±22.08 compared to 13.79±20.04. Decrement of skin resistance (Min SR-Mode SR) was -50.89±44.95 in hypoglycemic event group compared to -7.47±22.60 in non-hypoglycemic event group. All these physiologic changes were statistically significant with p-values= 0.015, 0.046 and 0.002 respectively. Conclusion: This is the first time a scoring system for hypoglycemic response from wearable devices has been used in Rajavithi Hospital.